Clientelism and dominant incumbent parties: party competition in an urban Turkish neighbourhood. Issue 1 (2nd January 2020) - Yıldırım, Kerem
ABSTRACT: Incumbent parties are often able to control state resources in ways that allow them to garner support in a clientelistic fashion. When regulatory institutions cannot restrain the incumbent's discretionary control over these resources, monopolistic control can give these parties a major political advantage. Focusing on clientelistic strategies employed by Turkey's ruling AK Party in comparison to opposition parties, this paper discusses mechanisms through which the incumbent party garners advantages through clientelism. While doing so, it presents evidence from an original fieldwork conducted in an Istanbul neighbourhood.